2014
DOI: 10.3329/bmj.v41i3.18959
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Surgical Outcome of Myringoplasty

Abstract: DOI: http://dx.doi.org/10.3329/bmj.v41i3.18959Bangladesh Medical Journal 2012 Vol.41(3): 45-48

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…Therefore it is preferable to make the ear dry preoperatively in order to achieve the best results. These findings were comparable to the studies of Pinar et al and Sarker et al 10,11 The success of hearing reconstruction of the hearing mechanism depends on the pre-operative ossicular status. An intact ossicular system with only a perforation in the tympanic membrane gives the best results.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore it is preferable to make the ear dry preoperatively in order to achieve the best results. These findings were comparable to the studies of Pinar et al and Sarker et al 10,11 The success of hearing reconstruction of the hearing mechanism depends on the pre-operative ossicular status. An intact ossicular system with only a perforation in the tympanic membrane gives the best results.…”
Section: Discussionsupporting
confidence: 90%
“…Another study by Md. Zakaria Sarker et al 5 showed majority of the patients (50%) were among the age group 26-35 years.…”
Section: Discussionmentioning
confidence: 91%
“…Zakaria Sarker et al the size of the perforation was graded as small (less than 50%), medium (50-75%) and large (> 75%). 5 In another study by Geetanjali Jaiswani and Rajesh Kumar had 21 (26.3%) small (0-25%) perforations, 27 (33.75%) medium-sized (26 -50%) perforations and 32 (40%) large (> 50%) perforations. 6 Most common approach used was transcanal (90% in group 1 and 83.3% in group 2) in our study.…”
Section: Discussionmentioning
confidence: 95%
“…In another study Alam et al showed the mean pre and post operative air conduction threshold in the successful grafting cases were 31.43 dB and 21.43 dB respectively with a mean audiological improvement of 10 dB & improvement of mean air bone gap was 10.83 dB 16 . 19,23 .…”
Section: Discussionmentioning
confidence: 99%